Effect of increasing hydrophilic-hydrophobic block length in quaternary ammonium-functionalized poly(ether sulfone) block copolymer for anion exchange membrane fuel cells - Sung, Seounghwa; Mayadevi, T. S.; Chae, Ji Eon; Kim, Hyoung-Juhn; Kim, Tae-Hyun (한국공업화학회, 2020)
Quaternary ammonium-functionalized poly(ether sulfone) (QA-PES) block copolymers with different block chain lengths were prepared as anion exchange membranes. Copolymers with similar hydrophilic/ hydrophobic block ratios and hence similar IEC values, but with various oligomer block chain lengths were synthesized to investigate, for the first time, how the length of each oligomer included in the block copolymers affected the chemophysical and electrical properties of the obtained QA-PES anion exchange membranes. The copolymer with the optimal hydrophilic:hydrophobic block chain length (QA-PES-16-30) showed good phase separation. This led to the optimal formation of ionic clusters, and the highest ion conductivity of 81.01 mS cm(-1) at 80 degrees C, as well as excellent physicochemical stability even after alkaline treatment in 1 M NaOH at 60 degrees C for 500 h, due to strengthening of the hydrophobic regions, strongly suggesting that the block chain length of each of the hydrophilic and hydrophobic blocks can affect the physicochemical properties of the polymer membranes. The H-2/O-2 single cell performance using the QA-PES-16-30 membrane showed a maximum power density of 260 mW cm(-2), much higher than that obtained from the Tokuyama A201. (C) 2019 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.